MANAJEMEN PEMBINAAN KARAKTER MELALUI PROGRAM TAHFIZ DI MTSS MU’ALLIMAT NW ANJANI - Annisya Muplihatin; Muhammad; Edy Muhammad Jayadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the management of student character development through the Tahfiz Program at MtsS Mu’allimat NW Anjani. The study focuses on the planning, implementation, and evaluation of the Tahfiz Program as an effort to shape students’ character. This research employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving the principal, teachers, Tahfiz teachers, and students as the research subjects. The findings revealed that: (1) the Tahfiz Program was implemented in a structured manner through activity scheduling, determination of memorization targets, and the provision of competent educators; (2) the implementation of the program was carried out through routine activities such as memorization submission, muraja’ah (memorization review), and character guidance integrated into the learning process; and (3) program evaluation was conducted periodically to assess students’ memorization achievements as well as their character development, including discipline, responsibility, and religious attitudes. Overall, the Tahfiz Program contributed significantly to the development of better student character